Classification of a Pedagogical Personality Historiography Sources - Lyudmyla Golubnicha (Pedagogical Discourse, 2013)
The article deals with the stage of Ukrainian pedagogical historiography development. The idea of the latter hase been represented. Peculiarities of conditional classification of pedagogical and historiography sources, which include the information about a pedagogical personality have been researched. The pedagogical historiography sources have been defined.Considerable attention is paid to the characteristics of the types, the sorts and the kinds of pedagogical and historiography sources, which have  the information about a pedagogical personality. Peculiar features of pedagogical historiography sources which are the foundation for a pedagogical personality research have been cleared up. Their importance for pedagogical historiographyhas been defined.